IMPLEMENTATION OF PUBLIC HEALTH POLICY IN THE NATIONAL HEALTH INSURANCE PROGRAM BY BPJS - Kurniati, Poni Sukaesih; Maulana, Syauqi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to determine the implementation of public policies in the health sector, with a focus on the implementation of the Health BPJS Program and its impact on community satisfaction. Within the framework of the national health insurance system in this country, the Health BPJS Program is one of the government’s initiatives that aims to provide equal access to health for all residents. This type of research uses qualitative research methods with a descriptive approach. By examining research data. Namely, books, articles and the internet. The public policy analysis approach is carried out through a review of policies and regulations related to the BPJS Health Program, including membership requirements, claims management, and service coverage. The results of public policy analysis show that there have been significant policy changes in recent years, such as expanding service coverage and improving claims management. The result of this research is to find out how successful the National Health Insurance process carried out by BPJS is. It is hoped that the government will pay more attention to the programs being implemented